Air Permeability and Acoustic Absorbing Behavior of Nonwovens (Journal of Fiber Bioengineering and Informatics, 2018)
Several nonwovens were studied to explore the relationship between their structural characteristics, permeability and acoustic absorbing behavior. Fundamental structural parameters including thickness, gram square meter and porosity were considered. Results show that the permeability is not just linear to porosity, but also related to many other complex and difficult-to-measure parameters. Further in this the paper we compared absorption coefficient of nonwovens with and without air permeability back, the sound absorption principles of those are completely different. For nonwovens with rigid back, the absorption coefficient increases with increasing thickness. For samples tested with air gap, the increasing air permeability moves the absorption curve towards lower frequency, and enhances the initial slopes of the curves. And also the absorption coefficients over the whole frequency range were found to increase with air permeability. This finding also indicates that the capillary effect alone cannot sufficiently explain the acoustic absorbing behaviour of nonwovens. Accurate theories which can illustrate sound absorption property of nonwovens still need to be improved and more precise model is still to be developed to explain the acoustic absorbing behaviour of nonwovens.